Climate change expected to drive habitat loss for two key herbivore species in an alpine environment. (2nd March 2015) - Parida, M.; Hoffmann, A. A.; Hill, M. P.
Abstract Aim Our first aim was to determine the environmental factors associated with two native Australian Lepidoptera species, Lomera caespitosae and Oncopera alpina, key herbivores of alpine and subalpine Poa grasses. Both species have been associated with areas of extensive grass death in Australian alpine regions, possibly affecting vegetation succession and recovery. Our second aim was to generate and evaluate potential distributional changes for both these moths and their host plants under scenarios of climate change. Location Alpine regions in south‐eastern Australia. Methods We surveyed alpine regions in south‐eastern Australia to compile presence–absence datasets for both moth species. We constructed ecological niche models from our survey data, in addition to predicting distributions of suitable host‐plant species for the moths. Grass damage sites attributed to the moths were used additionally as independent test datasets to validate model performance. Future effects on species distributions under climate change scenarios were then investigated. Results The environmental factors affecting distributions differed between the moth species; for example, precipitation variables appeared to be important for L. caespitosae, while low winter–spring temperatures were expected to limit O. alpina. The findings were related to the presence of grass damage, which was greater in areas where species distributions overlapped. A declining trend in suitability was predicted for both herbivore species under climate change, while Poa spp. distributions were expected to be less influenced by climate change. Main conclusions The distributions of both moth species are more likely to be restricted by climate than host‐plant availability. Predicted climate change effects are likely to put L. caespitosae under greater immediate risk of local extinction than O. alpina as a result of large areas of habitat loss by 2050.